2012
DOI: 10.1143/jpsj.81.064707
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study on the Structural and Magnetic Properties of Iron Hydride

Abstract: The magnetic and structural properties of iron hydride FeH with the double hexagonal close-packed (dhcp) and hexagonal close-packed (hcp) structures are investigated by first-principles density-functional theory calculations with a spin-polarized form of generalized gradient approximation. All the calculations are performed using all-electron fullpotential linearized augmented plane wave method. Both dhcp and hcp FeH are ferromagnetic at ambient pressure. The ferromagnetic ordering of the dhcp structure collap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
8
20
0
Order By: Relevance
“…Spectra at both pressures have similar (isomer) central shifts (CS) with respect to α‐iron at comparable pressure, are in reasonable agreement with the CS previously reported by Narygina et al () at 47 GPa, and are distinct from the central shift reported for either the dhcp or hcp phases (supporting information Table S2). In agreement with previous studies, the fcc phase of FeH X is not ferromagnetic, in contrast to that of the dhcp and hcp phases (Narygina et al, ; Tsumuraya et al, ), and as such SMS functions as a secondary confirmation of the structure of our samples, as there is no evidence of magnetic hyperfine field splitting in the measured spectra.…”
Section: Resultssupporting
confidence: 93%
“…Spectra at both pressures have similar (isomer) central shifts (CS) with respect to α‐iron at comparable pressure, are in reasonable agreement with the CS previously reported by Narygina et al () at 47 GPa, and are distinct from the central shift reported for either the dhcp or hcp phases (supporting information Table S2). In agreement with previous studies, the fcc phase of FeH X is not ferromagnetic, in contrast to that of the dhcp and hcp phases (Narygina et al, ; Tsumuraya et al, ), and as such SMS functions as a secondary confirmation of the structure of our samples, as there is no evidence of magnetic hyperfine field splitting in the measured spectra.…”
Section: Resultssupporting
confidence: 93%
“…The symmetry of one of these sites Neutron powder diffraction experiments performed on quenched FeD samples [25] showed that D atoms were positioned slightly off the center of the interlayer at z H = 0.882. This vertical displacement was confirmed for FeH by DFT calculations [26]. In the present study we first performed an energy minimization by relaxing the atomic positions of H atoms and found z H = 0.880, in good agreement with both experiment and previous calculations.…”
Section: B Computational Methodssupporting
confidence: 89%
“…359 DFT calculations predicted that metallic R3m and Im3m symmetry H 3 S phases became preferred above 111 and 180 GPa, respectively. The EPC of both structures was found to be particularly high, and the T c was estimated as being [155][156][157][158][159][160][161][162][163][164][165][166] GPa. The cubic Im3m structure is illustrated in Fig.…”
Section: Sulfurmentioning
confidence: 98%
“…The FM to NM transition of the hcp and dhcp phases of FeH under pressure have been studied via DFT calculations. 159 Recently, the FeH 5 phase illustrated in Fig. 7(d) was synthesized after laser heating in a DAC above 130 GPa.…”
Section: Group 8: Iron Ruthenium Osmiummentioning
confidence: 99%